Epidemiology, Clinical Features, and Outcomes of Hospitalized Adults with COVID-19: Early Experience from an Academic Medical Center in Mississippi. Issue 3 (March 2021) - Lucar, Jose; Wingler, Mary Joyce B.; Cretella, David A.; Ward, Lori M.; Sims Gomillia, Courtney E.; Chamberlain, Nicholas; Shimose, Luis A.; Brock, James B.; Harvey, Jessie; Wilhelm, Andrew; Majors, Lance T.; Jeter, Joshua B.; et al.
Abstract : Data on hospitalized patients with coronavirus disease 2019 in socioeconomically disadvantaged areas is urgently needed to guide public health policies for infection control in the community. In this retrospective cohort study, we describe the demographics, clinical characteristics, and outcomes of the initial group of hospitalized adults with coronavirus disease 2019 at the only academic medical center in Mississippi. Abstract : Objectives: To describe the demographics, clinical characteristics, and outcomes of hospitalized adults with coronavirus disease 2019 (COVID-19) in an academic medical center in the southern United States. Methods: Retrospective, observational cohort study of all adult patients (18 years and older) consecutively admitted with laboratory-confirmed severe acute respiratory syndrome-coronavirus-2 infection between March 13 and April 25, 2020 at the University of Mississippi Medical Center. All of the patients either survived to hospital discharge or died during hospitalization. Demographics, body mass index, comorbidities, clinical manifestations, and laboratory findings were collected. Patient outcomes (need for invasive mechanical ventilation and in-hospital death) were analyzed. Results: One hundred patients were included, 53% of whom were women. Median age was 59 years (interquartile range 44–70) and 66% were younger than 65. Seventy-five percent identified themselves as Black, despite representing 58% of hospitalized patients at our institution in 2019. Common comorbid conditions included hypertension (68%), obesity (65%), and diabetes mellitus (31%). Frequent clinical manifestations included shortness of breath (76%), cough (75%), and fever (64%). Symptoms were present for a median of 7 days (interquartile range 4–7) on presentation. Twenty-four percent of patients required mechanical ventilation and, overall, 19% died (67% of those requiring mechanical ventilation). Eighty-four percent of those who died were Black. On multivariate analysis, ever smoking (odds ratio [OR] 5.9, 95% confidence interval [CI] 1.2–28.6) and history of diabetes mellitus (OR 5.9, 95% CI 1.5–24.3) were associated with mortality, and those admitted from home were less likely to die (vs outside facility, OR 0.2, 95% CI 0.0–0.7). Neither age, sex, race, body mass index, insurance status, nor rural residence was independently associated with mortality. Conclusions: Our study adds evidence that Black patients appear to be overrepresented in those hospitalized with and those who die from COVID-19, likely a manifestation of adverse social determinants of health. These findings should help guide preventive interventions targeting groups at higher risk of acquiring and developing severe COVID-19 disease.